2006
DOI: 10.1002/anie.200600636
|View full text |Cite
|
Sign up to set email alerts
|

Titanium–Salan‐Catalyzed Asymmetric Epoxidation with Aqueous Hydrogen Peroxide as the Oxidant

Abstract: Keep it simple: A titanium complex with a salan ligand bearing phenyl groups at C3 and C3′ is an efficient catalyst for the enantioselective epoxidation of unfunctionalized olefins with aqueous hydrogen peroxide (see scheme); furthermore, the epoxidation was stereospecific. The C3 and C3′ substituents stabilize this complex and enhance the asymmetric induction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 167 publications
(59 citation statements)
references
References 28 publications
2
55
1
1
Order By: Relevance
“…Solche Reaktionen zeigen Potenzial für großtechnische Oxidationsprozesse,f ür die unkritische Ansätze gebraucht werden. [194] Bisher sind die so genannten Ti-Salalen-Komplexe [195] die enantioselektivsten Oxidationskatalysatoren. Ein besonderer Bereich der Forschung kçnnte daher die Verringerung der Komplexität des ursprünglichen Katalysators hin zu einfacheren Motiven sein, die bereits die gleiche oder eine bessere Leistung als der komplexe Ausgangskatalysator gezeigt haben.…”
Section: London'sche Dispersionunclassified
“…Solche Reaktionen zeigen Potenzial für großtechnische Oxidationsprozesse,f ür die unkritische Ansätze gebraucht werden. [194] Bisher sind die so genannten Ti-Salalen-Komplexe [195] die enantioselektivsten Oxidationskatalysatoren. Ein besonderer Bereich der Forschung kçnnte daher die Verringerung der Komplexität des ursprünglichen Katalysators hin zu einfacheren Motiven sein, die bereits die gleiche oder eine bessere Leistung als der komplexe Ausgangskatalysator gezeigt haben.…”
Section: London'sche Dispersionunclassified
“…However, recently the groupof Katsuki reported on a significant breakthrough in the field of titanium-catalyzed asymmetric epoxidation of nonfunctionalized alkenes [11][12][13]. The successful catalysts used in this system are based on a combination of titanium and reduced salen-type ligands (also known as salenan and salan, respectively).…”
Section: Epoxidations Of Alkenes Catalyzed By Early Transition Metalsmentioning
confidence: 99%
“…Hence, the chemoselectivity could to a certain point be controlled by the choice of additive. Ribas and Costas have studied manganese triflate complexes based on the 2-pyridyl derivative of TACN (12), and they found that complex 13 was a robust and active catalyst for the epoxidation of alkenes using peracetic acid as the terminal oxidant [53]. More recently, this catalyst was found to be compatible with aqueous hydrogen peroxide if the epoxidation reactions were performed with acetic acid (14 equiv.)…”
Section: Manganese-catalyzed Epoxidationsmentioning
confidence: 99%
“…On the basis of the hypothesis that a peroxotitanium complex 20 (Fig. 11.2 ), in which the amino proton of the ligand forms hydrogen bond with the peroxo ligand, is the active species for the reaction, the authors further explored titanium -based epoxidation catalysts and found that titanium (salan) complexes 21 promote the asymmetric olefi n epoxidation (Scheme 11.25 ) [39] . A brief screening of salan ligands disclosed that complex 21d bearing cyclohexanediamine moiety and phenyl groups at the C3 and C3 ′ positions exhibited high asymmetric catalysis.…”
Section: Titanium Catalystmentioning
confidence: 99%